Pelatihan Tata Kelola Manajemen Bisnis Digital Bagi Pengembangan Bisnis UMKM Kuliner Sate Bandeng - Gusmarani, Rica; Arianto, Bambang (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Abstract: The purpose of community service is to encourage the development of culinary Micro, Small and Medium Enterprises (MSMEs) in the governance of digital business management. The digital era requires MSME entities to be able to adapt to digitalization as a form of business scale development. Digitalization can make MSMEs compete with competitors and emphasize branding in the digital realm. In community service at MSME Sate Bandeng Bu Aliyah which was carried out on November 12, 2024, assistance was provided regarding digital business management governance which includes social media marketing, digital financial governance, digital business management to digital-based product branding. The success of this activity can be seen from the increasing knowledge and understanding of the owners and staff of the culinary MSME Sate Bandeng Bu Aliyah Serang Banten. From the results of this community service activity, it is known that the owner of the culinary MSME Sate Bandeng Bu Aliyah has been able to carry out digital business management governance well with a success rate of 80 percent so that it can strengthen the scale of business development.